Residual-Based Algorithm for Growth Mixture Modeling: A Monte Carlo Simulation Study - Marcoulides, Katerina M.; Trinchera, Laura (Frontiers in Psychology, 2021)
Growth mixture models are regularly applied in the social and behavioral sciences to identify unknown heterogeneous subpopulations that follow distinct developmental trajectories. Marcoulides and Trinchera (2019) recently proposed a mixture modeling approach that examines the presence of multiple latent classes by algorithmically grouping or clustering individuals who follow the same estimated growth trajectory based on an evaluation of individual case residuals. This article presents the results of a simulation study that examined the performance of this new approach for determining the number of classes in growth mixture models. The performance of the approach to correctly identify the number of classes is examined under a variety of longitudinal data design conditions. The findings demonstrated that the new approach was a very dependable indicator of classes across all the design conditions considered.